2016
DOI: 10.1186/s41476-016-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide nano-composites layer on fiber optic tip sensor reflectance response for sensing of aqueous ethanol

Abstract: In this study, the used of tapered optical fiber tip as sensors coated with reduced Graphene Oxide (rGO) is investigated. The resultant rGO nanocomposites coated on the tapered fiber sensor were characterized by X-ray Diffraction (XRD), Raman spectroscopy, and field emission scanning electron microscopy (FESEM). Optimization of the rGO layer and the tapering parameters are found and the sensing capability of the device is tested using different concentrations of ethanol in water. The nanocomposite layer improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…The positions of D-and G-band are significantly dependent on the defects, edges, disorder, grain size and microstructure of the graphene materials. The D-band of graphene indicates to the defects and G-band represents the sp 2 atomic arrangement of carbon atoms of graphene layers [26,27]. The relative intensity ratio ID / IG for rGO was found to be 1.295 indicates the presence of defects in rGO film [28].…”
Section: Methodsmentioning
confidence: 97%
“…The positions of D-and G-band are significantly dependent on the defects, edges, disorder, grain size and microstructure of the graphene materials. The D-band of graphene indicates to the defects and G-band represents the sp 2 atomic arrangement of carbon atoms of graphene layers [26,27]. The relative intensity ratio ID / IG for rGO was found to be 1.295 indicates the presence of defects in rGO film [28].…”
Section: Methodsmentioning
confidence: 97%
“…The S3 peak on the other hand arises from incomplete activated phonon groups [31]. The final peak at 950 cm −1 can be attributed to the second-order Raman scattering effect of silicon [31,32]. The silicon peak is present due to the silicon substrate base which was used during the characterization of the rGO sample, though it has no effect on this work.…”
Section: Characterization Of Reduced Graphene Oxidementioning
confidence: 90%
“…These are identified as the 2D and S3 peaks respectively, with the 2D peak being an overtone of the D peak, and arising due to the sp 2 hybridization of the carbon atoms (C-C) in the graphene nanostructure [30]. The S3 peak on the other hand arises from incomplete activated phonon groups [31]. The final peak at 950 cm −1 can be attributed to the second-order Raman scattering effect of silicon [31,32].…”
Section: Characterization Of Reduced Graphene Oxidementioning
confidence: 99%
“…The fiber tips were coated with rGO by drop casting and acted as the sensing layer for ethanol. The reflectance response of the rGO coated fiber tip reduced linearly, upon exposure to ethanol concentrations ranging between 20–80% [ 101 ]. Zhang et al reported a polymer optical fiber with graphene film deposited on the distal end of the optical fiber as an acetone sensor [ 102 ].…”
Section: Graphene-based Optical Sensorsmentioning
confidence: 99%